LENGUAGE AND INTERCULTURAL COMMUNICATION - To‘ychiyeva Sayyora Aliyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article highlights how useful language and culture are for humanity and how important they are for learning languages. It is clear that language and communication are essential tools in the modern world. The novelty of the article is the development of the language and cultural skills of students. The article proves that the analyzed language and culture can be used as practical and theoretical material in the educational process.